On the Essential Unpredictability of Certain Human Actions and Certain Mechanical Processes in Certain Deterministic Systems - Zak, Gad (My University, 1980)
This work deals with the impossibility of full and precise prediction even of a domain of prediction which is supposed to be completely (metaphysically) determined by physical relations and regularities, and regardless of quantum mechanical limitations. The Laplacian notion of an Intelligence capable of complete prediction based on complete information is explored and shown to be impossible. It is further suggested that the impossibility of full prediction even of completely (metaphysically) determined systems, referred to as the property of "impredictfulness", bears striking similarities to the limitative results of Turing, Gödel and Tarski, regarding computational, syntactical and semantical properties of formal systems.
Keywords: Philosophy; Philosophy